2004
DOI: 10.1016/j.watres.2004.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Integrated real-time control strategy for nitrogen removal in swine wastewater treatment using sequencing batch reactors

Abstract: A new integrated real-time control system was designed and operated with fluctuating influent loads for swine wastewater treatment. The system was operated with automatic addition control of an external carbon source, using real-time control technology, which utilized the oxidation-reduction potential (ORP) and the pH as parameters to control the anoxic phase and oxic phase, respectively. The fluctuations in swine wastewater concentration are extreme; an influent with a low C=N ratio is deficient in organic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(48 citation statements)
references
References 14 publications
0
47
0
1
Order By: Relevance
“…Anaerobic treatment can be used to generate methane gas, but ammonia and odor-producing chemicals are not fully removed. Thus, while such treatment methods can be effective, they can still be energy demanding or result in generation of nuisance odors (4,13).…”
mentioning
confidence: 99%
“…Anaerobic treatment can be used to generate methane gas, but ammonia and odor-producing chemicals are not fully removed. Thus, while such treatment methods can be effective, they can still be energy demanding or result in generation of nuisance odors (4,13).…”
mentioning
confidence: 99%
“…As shown in the figure, 5 min after feeding began (point A), the anoxic phase had started. Point B represents the nitrate knee in the ORP curve, which is the point at which the complete removal of nitrate occurred [23]. Point C signifies the beginning of the aerobic phase.…”
Section: Real-time Strategy For Foam Controlmentioning
confidence: 99%
“…It was found that the use of external carbon sources [20][21][22][23] in the reactor was a viable method of enhancing sequencing batch reactor (SBR) performance. In this study, the relationship between incomplete denitrification caused by a low C/N ratio and sludge foaming was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing batch reactor (SBR) has been frequently applied in CAFOs to treat swine wastewater and proved to be effective in decomposing ordinary organic materials as expressed by chemical oxygen demand (COD) (Dosta et al, 2008;Kim et al, 2004). However, to date, the fate and behavior of antibiotics in the SBR for swine wastewater treatment still remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%